O sujeito de uma língua estrangeira: o deslizamento do significante no sujeito paranoico - Souza, Raquel Shirley Ferreira de (2012)
This dissertation work sought, through the distinctive language of paranoia, a dialogue between the language on psychoanalysis and the language on linguistics. For do this, emphasized the saussurian concepts were important to comprehend the core theme of the subject of a foreign language as absolut, associative relations, syntagmatic, significant language as the social part of language and speech as the distinctiveness of being verbose. Was made a counterpoint to these concepts to the Lacan‘s theory – the unconscious is structured like a language – that identifies the highest primacy the clinic with symbolic as wel as the Lacan‘s last teaching, which speculates about the lalangue, the language of the unconscious. From the delirium, from the perspective of psychoanalysis, was tried to comprehend the constitution of language assomethig external to the subject, and what the outline made by paranoid to do short excursions on their social connections, what is the status of invention and how it‘s thought, being based on saussurean linguistics.